A Joint Source-Channel Video Coding Scheme Based on Distributed Source Coding - Zhang, Yixuan; Zhu, Ce; Yap, Kim-Hui (IEEE transactions on multimedia, 2008)
Recently, several error resilient schemes have been proposed to tackle the error propagation problem in the motion-compensated predictive video coding based on a promising technique - distributed source coding (DSC). However, these schemes mainly apply the distributed source codes for channel error correction, while under-utilizing their capability for data compression. A channel-aware joint source-channel video coding scheme based on DSC is proposed to eliminate the error propagation problem in predictive video coding in a more efficient way. It is known that near Slepian-Wolf bound DSC is achieved using powerful channel codes, assuming the source and its reference (also known as side-information) are connected by a virtual error-prone channel. In the proposed scheme, the virtual and real error-prone channels are fused so that a unified single channel code is applied to encode the current frame thus accomplishing a joint source-channel coding. Our analysis of the rate efficiency in recovering error propagation shows that the joint scheme can achieve a lower rate compared with performing source and channel coding separately. Simulation results show that the number of bits used for recovering from error propagation can be reduced by up to 10% using the proposed scheme compared to Sehgal-Jagmohan-Ahuja's DSC-based error resilient scheme.